From Smith to Smickle: The Charter’s Minimal Impact on Mandatory Minimum Sentences - Parkes, Debra (2012)
This paper attempts to assess the impact that the Canadian Charter of Rights and Freedoms has had, and may have in the near future, on mandatory minimum sentences and their proliferation in Canadian law. To answer those questions, the paper will first briefly review the Supreme Court case law on the constitutionality of mandatory minimum sentences. The next two sections will outline the approach taken in the recent Smickle decision, in which a mandatory minimum sentence was declared invalid under the Charter, and will argue that courts should subject the purported goals, justifications and impacts of mandatory minimum sentences to a more searching form of Charter scrutiny as we enter the fourth decade of the Charter’s operation